The phoenix and the carpet - Nesbit, E. (Edith), 1858-1924.; Millar, H. R. (New York : Puffin, 1994)
Cyril, Anthea, Robert, Jane, and their baby brother are longing for excitement when they discover that the carpet Mother bought in a junk shop is the answer to their prayers.
Sequel to: Five children and it.
6.0
Young Adult
Keywords: Carpets -- Juvenile fiction; Time travel -- Juvenile fiction; Carpets -- Fiction; Time travel -- Fiction; Rugs and carpets -- Fiction; Time travel -- Fiction